Conditions for the Development of Public-Private Partnership PPP - Analysis Based on an Example of Transport Infrastructure in Poland - Beata Zagozdzon (Communications - Scientific letters of the University of Zilina, 2020)
Transport infrastructure is not currently the domain of activity of solely the public sector. Governments entrust the provision of services or realization of investment tasks to private entities and the form of involvement of private investors may be the public-private partnership PPP. Successful implementation of the PPP projects requires appropriate economic, legal, institutional and social conditions.The article identifies these determinants based on the literature on the subject and then their analysis in relation to conditions of operation and market development of the PPP projects in the area of transport infrastructure in Poland. The analysis covered the years 2009-2018 and was conducted against the background of development of the PPP market in selected EU countries.